Moderating Effect of Individualism Orientation on the Employees' Responses to Leader's Reward and Punishment Behavior in China - ZHOU NA (The Graduate School, Ajou University, 2015)
The purpose of the study is testing a relationship between leader reward and punishment behaviors and employees’ work-related attitudes will be moderated by the individualism as an individual variable. In this study, the main effects of leader reward and punishment behaviors to employees’ work-related attitudes were examined. I further tested whether the individualism orientation will affect these relationships between leader reward/punishment behavior and employees’ work-related attitudes.
학위논문(석사)--아주대학교 일반대학원 :경영학과,2015. 2
Keywords: leader reward; punishment behaviors